RANCANG BANGUN PINTU WAHANA OTOMATIS MENGGUNAKAN SENSOR ULTRASONIK HC-SR04 SEBAGAI PENGUKUR TINGGI BADAN DAN SENSOR LOAD CELL DENGAN HX711 SEBAGAI PENGUKUR BERAT BADAN BERBASIS ARDUINO MEGA 2560 - Lutfiyanto, Agung Hanifan; Subari, Arkhan (Gema Teknologi, 2017)
Agung Hanifan Lutfiyanto, Arkhan Subari, in this paper explain that at present, profit plyaground still uses manual measurement to select visitors who will enter the vehicle. Measuring just selecting one's height by putting aside weight can have a negative impact on the smoothness and safety of the playing area. Therefore, an automation is needed to measure body weight and height to be safer from game accidents and increase vehicle life to avoid damage. This design makes the device an automatic vehicle area entrance system using Arduino Mega 2560 for the main controller system supported by various sensors namely HC-SR04 ultrasonic sensor as a measure of prospective visitor height, 100 Kg Load Cell sensor as a measure of prospective visitor's weight and motor servo as the opening and closing door of the vehicle. When prospective visitors will enter the vehicle, prospective visitors stand on their height and weight gauges. Furthermore, Arduino compares with the standard height and weight previously set. If the weight and height are in accordance with the standard, the door will open automatically and visitors can enter the vehicle. For testing the prospective visitor's height as measured by the HC-SR04 ultrasonic sensor has an average error ratio of 1.01%, while testing prospective visitor's weight measured by sensor Load Cell has an average error ratio of 2.90% and is calculated quite accurate.